Reinterpreting Constitutional Law through the Lens of Islamic Sufism: A Theosophical Approach to Governance and Legal Principles - Bidabad, Bijan (Fakultas Syariah INSURI Ponorogo, 2024)
The fundamental principles of constitutional law are outlined concisely, though they are reinterpreted in this work through the philosophical lens of Sufism. While these principles are traditionally embedded in constitutional texts, they are reconceptualised here based on Sufi thought. Key concepts such as popular sovereignty, limitations on power, accountability of the governing bodies, separation and independence of powers, power equilibrium, central authority supremacy, transparency in governance, adherence to legal norms, and the mechanisms of checks and balances are critically examined. This study investigates the theoretical underpinnings of constitutional law from the theosophical and mystical perspectives of Islamic Sufism. By introducing ten foundational principles, the research aims to establish a robust framework for formulating and enhancing constitutional systems. Comparative analyses with Gnostic traditions from other religions could provide further insights. These principles offer valuable perspectives for academic discourse and have practical implications for advancing constitutional law and its reinterpretation. The inherent subtlety, sincerity, and ethical depth of Islamic Sufism provide a compelling perspective that may intrigue legal scholars and researchers. Despite its richness, the Sufi viewpoint still needs to be explored within public law studies. This paper introduces a novel and intellectually stimulating domain, inviting further scholarly inquiry.